2020
DOI: 10.1088/1757-899x/712/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Strength Properties of Porous Concrete Pavement Blended with Nano Black Rice Husk Ash

Abstract: In order to improve the porous concrete pavement strength, one of the elements in the porous concrete structure that needs to be considered is the cement paste binder. This study aimed to evaluate the strength properties of porous concrete pavement blended with nanoparticle from black rice husk ash (BRHA). The performance was evaluated based on compressive strength, density, age of curing and strength activity index. Four nano BRHA replacement levels were considered in the study, i.e. 10%, 20%, 30%, and 40% by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…After 28 days, the slowest reaction occurs leading to post-enhance the compressive strength of the cements. Furthermore, it can be observed that a higher amount of BRHA added to the cement results in lowering the compressive strength, which agrees well with other researches [9,10,[14][15][16]. This is probably because the increment of silica to alumina ratio (SiO2/Al2O3) in concrete due to the large amount of SiO2 in BRHA exhibits the geopolymer reaction and the gelation process [16].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…After 28 days, the slowest reaction occurs leading to post-enhance the compressive strength of the cements. Furthermore, it can be observed that a higher amount of BRHA added to the cement results in lowering the compressive strength, which agrees well with other researches [9,10,[14][15][16]. This is probably because the increment of silica to alumina ratio (SiO2/Al2O3) in concrete due to the large amount of SiO2 in BRHA exhibits the geopolymer reaction and the gelation process [16].…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, as BRHA prepared from agricultural waste is almost costless, the partial replacement of cement can lower the concrete construction cost. Recent literatures [9,10] have reported that the increase in RHA used in cement led to a decrease in concrete compressive strength, so the acceptable replacement ratio must be considered. Moreover, the effects of BRHA replacement on corrosion and chloride penetration are also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…During the technology development, the quality of PCPs is increasing with the improvement of their compressive strength and noise reduction. PCPs, in contrast to conventional concrete pavement, have a high percentage of voids, between 15% and 25% [14]. Figure 2 shows the position of voids spaces,coarse aggregates and cement paste in PCPs.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Since the use of pozzolans usually reduces the compressive strength of concrete, in order to reduce this negative effect, nanoparticles are used in concrete [14]. Nanoparticles can increase the density of particles in concrete, thereby increasing the density of nanostructures in concrete and improving its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%